Excessive body mass and obesity as a cause of progression of endogenous intoxication in patients with non-alcoholic fatty liver disease - Filippova, A. Yu. (Zaporozhye Medical Journal, 2016)
Aim – to study the features of indicators of endogenous intoxication (EI), depending on the body mass index (BMI) in patients with excessive body mass (EBM) and obesity (OB) in combination with nonalcoholic hepatic steatosis (NAHS) and nonalcoholic steatohepatitis (NASH). Materials and methods. The study involved 200 patients with OB in conjunction with non-alcoholic fatty liver disease and BT pathology, who at the time of sonographic and morphological study of liver biopsy revealed signs of hepatic steatosis. Depending on the degree of increase in BMI of all patients with OB and NAHS (n=100) and NASH (n=100) were divided into three groups: 1 group – EBM; 2 group – OB I degree; 3 group – OB II degree. The control group consisted of 20 practically healthy persons (PHP). Indicators of EI were determined by the content of middle weight molecules (MWM), their fractional composition: MWM-λ-210, MWM-λ-254, MWM-λ-280, concentration of copper (Cu) in serum of blood. Results. The content of MWM, MWM-λ-210, MWM-λ-254, MWM-λ-280, and Cu in the serum of patients with the EBM and OB in combination with NAHS and NASH were significantly increased relative to PHP in the presence of EBM and OB I degree (from p<0.05 to p<0.001), with higher values of EI indicators in patients with OB II degree. Conclusion: Rises in the level of EI in patients with the OB in combination with a NAHS and NASH and pathology BT have expressed significant dependence on the increase of the BMI parameters.